Age estimation, corroboration and back-calculation of four-spot megrim (Lepidorhombus boscii) on the Porcupine Bank using otoliths - Landa, Jorge; Hernández, Carmen (Estuarine, Coastal and Shelf Science, 2020)
Age and growth of four-spot megrim (Lepidorhombus boscii) at the Porcupine Bank, an important European demersal fisheries area, was estimated for the first time based on the analysis of 1334 otoliths. The state of the stock in the Celtic Seas (including the Porcupine Bank) and the northern Bay of Biscay (Div. 7.b-k and 8.a,b,d) has been recently assessed in ICES mainly based on survey abundance indices, but biological information for a forthcoming age-structured stock assessment process is required. In this study, age was estimated by counting the translucent bands (annuli) of the sagittal otoliths following internationally standardized protocols. Otoliths were obtained from specimens caught during five annual bottom trawl surveys (2008–2012) carried out at the Porcupine Bank. Consistency in age interpretation of four-spot megrim was demonstrated by analyzing the regularity of the distances of the annuli to the otolith's primordium and by the back-calculation of the annuli. The growth patterns obtained from direct otolith age estimation and from back-calculation were also compared. Age estimation was corroborated by tracking year-class abundance indices from the surveys. The strength of the year-classes was well tracked in abundant first age groups, highlighting the very abundant 2008 year-class. Furthermore, the von Bertalanffy growth parameters by sex and for combined sexes were also estimated and compared with those from other stocks. The results obtained for these parameters in the combined sexes direct age estimation, their back-calculation and the combination of both methods (L∞: 50.093; k: 0.126; t0: 0.296) will allow the upcoming age-structured assessment of this stock and thus a suitable population management. The strength of the cohorts here obtained was compared with those from a previous study in the Iberian Atlantic (8.c, 9.a) stock and based on age estimates calculated with the same ageing criterion. The differences in demographic structure and cohort dynamics found between stocks support the ...